Implementation of quasi-z source inverter for grid connected PV based charging station of electric vehicle - D Sattianadan; K Saravanan; S. Murugan; N. Hari; P. Venkadesh (Institute of Advanced Engineering and Science, 2019)
In recent trends, the use of electric vehicles is taking a sudden hike as they seem to be a much more friendly for the environment as compared to the conventional vehicles that run on combustion engines for a mode of transportation. With the increasing popularity of electric vehicles, the demand on the utility grid is also increasing. To overcome this problem, other alternative sources of energy need to be considered. Photovoltaic energy as the solution is finding its place in the EV charging systems. However, the total amount of energy that can be generated from the PV system is constrained, based on many parameters such as solar radiation, availability of space for Solar power plant development, maintenance of the system, etc. Hence, to maintain the continuity of the system, it needs to be integrated with the grid as well. This offers a smooth charging operation for the electric vehicles. In this paper, a new method is introduced for the integration between the solar inverter system and the utility transmission grid. Quasi-Z-source topology is proposed for the system integration. This topology facilitates a bidirectional flow of power between the PV source, the storage unit and the utility grid. The greatest advantage of this topology is its flexibility with different voltage levels of the solar inverter DC connection and the storage battery which requires no circuit alteration for charging batteries of different ratings. The hardware for the system is also fabricated. The results demonstrate that the proposed topology fits the generalized requirements.